Product development for the service sector : lessons from market leaders - Cooper, Robert G. (Perseus Books CambridgeUS, 1999)
Presents a comprehensive approach to product development tailored specifically for the dynamics of service industries. Identifies the nine critical steps for achieving project success - from doing solid 'up-from' homework to ensuring a quality launch effort.